Enhanced physical performance, attention, and mood states after a nap opportunity following a sleep restriction night in female athletes: A randomized controlled trial - BenSalem, S.; Salem, A.; Boukhris, O.; Ammar, A.; Souissi, N.; Glenn, J. M.; Jahrami, H.; Trabelsi, K.; Chtourou, H. (Journal of Sports Sciences, 2025)
This study examined the effects of two nap durations (40 minutes (N40) and 90 minutes (N90)) on physical performance, sleepiness, attention, mood states (Profile of Mood States, POMS), perceived exertion (RPE), pain perception (PP), recovery (PRS), and delayed onset muscle soreness (DOMS) in well-trained women. Fourteen female boxers underwent the digit cancellation test, POMS, and the 5-meter shuttle run test (5mSRT) under no-nap (N0), N40, and N90 conditions after either normal sleep (NSN) or sleep restriction (SRN). RPE and PP were assessed immediately post-5mSRT, while PRS and DOMS were recorded at 5 min and 24 h post-5mSRT. Total distance (TD) and higher distance (HD) were better in N40 and N90 after NSN compared to SRN (p < 0.05). Fatigue index (FI) was lower in N40 and N90 than in N0, and lower in N90 than N40 (p < 0.05). PRS improved and RPE, DOMS, and PP decreased significantly after N40 and N90 compared to N0, with N90 showing greater benefits (p < 0.05). Total POMS scores were better after N40 and N90 than N0, with N90 outperforming N40 (p < 0.05). Overall, N90 provided greater benefits than N40 in enhancing physical performance, attention, recovery, and mood, while reducing exertion, pain, and soreness after both NSN and SRN.